The Basics of Caring Research - Uusiautti, Satu; Määttä, Kaarina (Bold visions in educational research, 2016)
"What is caring research and how to conduct it? This book defines the new concept of caring research as a combination of two perspectives. Caring research means research that aims to promote well-being. It is focused on a good quality of life, human strengths and active life, as well as characteristics and positive development in human beings that act as buffers against malaise and help coping with adversities in life. In addition, caring research cares for the researcher well-being. Caring research is conducted by people who share the passion and enthusiasm to influence positively and collaborate. Caring research includes the joy of working and researching together. Thus, caring research is manifested in the relationships between researchers, supervisors, students, and other experts, and their mutual open and respectful interaction. The Basics of Caring Research analyzes these two elements of caring research through several viewpoints that are to illustrate the manifold nature of caring research as positively-focused and positively-conducted research. The book also includes critical analysis of the current requirements and future challenges of caring research. The book serves as a text book in, for example, research studies in psychology and educational and behavioral sciences. Researchers and supervisors find it a useful tool to support their supervision of various academic theses."--Publisher's description